2018
DOI: 10.1037/xhp0000538
|View full text |Cite
|
Sign up to set email alerts
|

Can vigilance tasks be administered online? A replication and discussion.

Abstract: Recently, experimental studies of vigilance have been deployed using online data collection methods. This data collection strategy is not new to the psychological sciences, but it is relatively new to basic research assessing vigilance performance, as studies in this area of research tend to collect data in the laboratory or in the field. The present study partially replicated the results of a newly developed online vigilance task (Thomson, Besner, & Smilek, 2016). A sample of 130 participants completed the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 35 publications
(86 reference statements)
0
23
0
Order By: Relevance
“…Moreover, Fraulini et al (2017) pointed out that in Thomson et al (2016) the vigilance task was performed online and outside the lab, without controlling the experimental context. Notwithstanding, Thomson et al outcomes were replicated later in a study conducted under the typical lab conditions (Claypoole et al, 2018). Indeed, we have recently analyzed the reliability of the vigilance and attentional components of the ANTI-Vea in a study with a large sample (N = 617), wherein participants either performed the standard ANTI-Vea in the lab or the online version (https://www.ugr.es/~neurocog/ANTI/) outside the lab in a suitable place of their choosing (Luna, Roca, Martín-Arévalo, & Lupiáñez, 2020).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, Fraulini et al (2017) pointed out that in Thomson et al (2016) the vigilance task was performed online and outside the lab, without controlling the experimental context. Notwithstanding, Thomson et al outcomes were replicated later in a study conducted under the typical lab conditions (Claypoole et al, 2018). Indeed, we have recently analyzed the reliability of the vigilance and attentional components of the ANTI-Vea in a study with a large sample (N = 617), wherein participants either performed the standard ANTI-Vea in the lab or the online version (https://www.ugr.es/~neurocog/ANTI/) outside the lab in a suitable place of their choosing (Luna, Roca, Martín-Arévalo, & Lupiáñez, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…Importantly, FA computed from the lure trials showed a prominent decrement across time on task, and consequently, the vigilance decrement was observed as an increment in the response bias and not as a loss in sensitivity (Thomson et al, 2016). Note that the results observed by Thomson et al were later replicated using the same vigilance task in a recent study conducted by Claypoole, Neigel, Fraulini, Hancock, & Szalma (2018).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In this paper, we hypothesize that performing semantic vigilance task weakens connectivity network of full spectrum at range (0.5-30) Hz as time passes. Semantic vigilance tasks require participants to attend to and process characters, symbols, text-speak words, words, or non-words over extended periods of time [46,47]. The semantic vigilance tasks require operators to respond to targets that are semantic or lexical in nature and withhold response to neutral stimuli, which are not semantically representative or related to target signals.…”
Section: Introductionmentioning
confidence: 99%
“…Neutral stimuli are not semantically related to lures or targets and include nonanimal objects such as "cube," "binder," or "socket." The inclusion of lures increases the difficulty associated with the semantic vigilance task (Claypoole et al, 2018;, whereas standard semantic vigilance tasks are easier in that they require only binary distinctions from participants (Fraulini et al, 2017). In the present study, the standard semantic vigilance tasks consisted of 10 targets and 90 neutral stimuli (referred to as "distracters" in Thomson et al, 2016), or 100 events per period.…”
Section: Task Types and Stimulimentioning
confidence: 75%